2014
DOI: 10.4236/as.2014.514162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Stress on the Citric Acid Metabolism Related Gene Expression in the Ponkan Fruits

Abstract: To explore the influence of water stress on fruit quality and gene expression related to citrate metabolism of ponkan. The test were conducted from May 15 to December 24 in 2013 using six-year-old ponkan (C. blanco cv. Ponkan) trees with 40% soil water conditions by taken regular watering as control. The content of acids in fruit were determined by HPLC, and relative expression of related genes of citric acid metabolic were determined by relative fluorescence quantitative PCR. The results showed that the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(9 reference statements)
2
4
0
Order By: Relevance
“…In this study, the changes of the relative gene expression level of SDH or DQS is consistent with the activities of NADP-QDH and NADP-SDH, but not exactly consistent with the content of quinic acid at early periods (20~35 DAF) of fruit development. The relative gene expression level of SDH was significantly positively correlated with the activities of NADP-QDH and NADP-SDH, which is consistent with the results on Citrus [16,40]. These results suggested that quinic acid may be synthesized at the early periods of fruit development and the activities of NADP-QDH and NADP-SDH may be regulated by SDH gene, DQS gene did not have a decisive effect on the quinic acid accumulation in the fruit of 'Ganmi 6'.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, the changes of the relative gene expression level of SDH or DQS is consistent with the activities of NADP-QDH and NADP-SDH, but not exactly consistent with the content of quinic acid at early periods (20~35 DAF) of fruit development. The relative gene expression level of SDH was significantly positively correlated with the activities of NADP-QDH and NADP-SDH, which is consistent with the results on Citrus [16,40]. These results suggested that quinic acid may be synthesized at the early periods of fruit development and the activities of NADP-QDH and NADP-SDH may be regulated by SDH gene, DQS gene did not have a decisive effect on the quinic acid accumulation in the fruit of 'Ganmi 6'.…”
Section: Discussionsupporting
confidence: 86%
“…Nowadays, there is a wide range of reports about the mechanism of organic acid metabolism during fruit development and maturation [26,30,31,[40][41][42][43][44]. The shikimate pathway is an important metabolic pathway present in plants, and is the main bridge connecting sugar metabolism and secondary metabolism [28].…”
Section: Discussionmentioning
confidence: 99%
“…A low soil water content causes drought and salt stress in citrus plants, resulting in reduced plant growth and leaf area, which ultimately affects photosynthesis, respiration, and metabolite profiles [40][41][42]. Moderate drought stress decreases the content of citric and malic acids in fruits such as nectarines [43] and grapes [44], which is in line with our results (Figure 3), whereas the opposite was reported for ponkan fruits grown in soil with 40% maximum water capacity under water stress [45]. In bitter oranges, drought and salinity stress increase the content of terpenes and flavonoids in the leaves [46] but decrease the fatty acid content in the roots [47].…”
Section: Discussionsupporting
confidence: 90%
“…CitNAC62 and CitWRKY1 could transactivate the promoter of CitAco3, then improv the expression of CitAco3 to control the degradation of citric acid in citrus fruit [ 39 ]. Zhang et al [ 3 ] found that 40% soil water stress treatment could significantly inhibit the expression of CitIDHs in Citrus fruit, and citric acid content was significantly increased, which was 66.3% higher than that of the control. The expression of CitGAD4 and CitGAD5 in citrus fruit was inhibited under the stress of water stress, and the degradation of citric acid was blocked and the organic acid was accumulated, which indicated the important role of GABA cycle on citric acid degradation in citrus fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Ponkan ( Citrus reticulata Blanco) is one of the main mandarin citrus in China, the fruit are rich of organic acid [ 2 ]. Zhang et al [ 3 ] have demonstrated that citric acid was the major organic acid in Ponkan fruit, which accountings for 91.82% of the total content in single fruit. During the storage period, the content of organic acids in fruit not only affected fruit flavor and quality, but also affected the storage characteristics of fruit [ 4 ].…”
Section: Introductionmentioning
confidence: 99%